Pengaruh E-Wom, Persepsi Harga dan Kualitas Produk Terhadap Keputusan Pembelian - Ariwangsa, I G.N. Oka; Lasmi, Ni Wayan; Darma, I Made Riski Aditya (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2023)
This study aims to determine the effect of electronic word of mouth, price perceptions, product quality partially and simultaneously on purchasing decisions. The sample in this study were 110 people. Data anal ysis techniques using validity test, reliability test, classic assumption test, multiple linear regression analysis, coefficient of deattermination test, F test and t test. From the research results, it was found that electronic word of mouth had a signifi cant positive effect on purchasing decisions, price perceptions had a significant positive effect on purchasing decisions, product quality had a significant positive effect on purchasing decisions and electronic word of mouth, perceived price and product quality had a significant effect on purchasing decisions. The magnitude of the influence of independent variables simultaneously on purchasing decisions is 63.5%, based on the measurement of the coefficient of determination .